2012
DOI: 10.1289/ehp.1104522
|View full text |Cite
|
Sign up to set email alerts
|

Phthalates and Perfluorooctanesulfonic Acid in Human Amniotic Fluid: Temporal Trends and Timing of Amniocentesis in Pregnancy

Abstract: Background: Measures of prenatal environmental exposures are important, and amniotic fluid levels may directly reflect fetal exposures during hypothesized windows of vulnerability.Objectives: We aimed to detect various phthalate metabolites and perfluorooctanesulfonic acid (PFOS) in human amniotic fluid, to study temporal exposure trends, and to estimate potential associations with gestational week of amniocentesis and maternal age and parity at amniocentesis.Methods: We studied 300 randomly selected second-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 43 publications
5
92
3
Order By: Relevance
“…PFCs cross the placenta, but umbilical cord concentrations have in most studies been lower than those observed in maternal serum or plasma (Inoue et al 2004;Fromme et al 2010;Jensen et al 2012;Gützkow et al 2012). In the present study, we found higher levels of PFCs in maternal serum than in cord serum, which is consistent with previous studies (Monroy et al 2008;Hanssen et al 2010;Beesoon et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PFCs cross the placenta, but umbilical cord concentrations have in most studies been lower than those observed in maternal serum or plasma (Inoue et al 2004;Fromme et al 2010;Jensen et al 2012;Gützkow et al 2012). In the present study, we found higher levels of PFCs in maternal serum than in cord serum, which is consistent with previous studies (Monroy et al 2008;Hanssen et al 2010;Beesoon et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, a new study by Chen et al (2012) found an inverse association between PFOS levels and gestational age. PFC levels increase in fetuses as pregnancy progresses as a recent study by Jensen et al (2012) showed that PFOS increased in amniotic fluid by gestational week. Advancing gestational duration might therefore result in decreased maternal body burden of PFCs.…”
mentioning
confidence: 97%
“…Thus, a number of chemicals measured in maternal urine, serum and breast milk have also been found in amniotic fluid, cord blood and meconium (Ikezuki et al 2002, Main et al 2006, Barr et al 2007, Jensen et al 2012. A recent study has reported detectable levels of metabolites from two common phthalate diesters, di(2-ethylhexyl) (DEHP) and di-isononyl phthalate (DiNP), and perfluorooctanesulfonic acid in amniotic fluid collected from Danish women (Jensen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, since our maternal serum levels were similar to those Abbreviations: LOD, limit of detection; SD, standard deviation. cord blood levels, and to levels in amniotic fluid (Jensen et al, 2012), this indicates that fetuses are not protected from maternal exposure, and that maternal serum levels could be used as markers of fetal exposure. Although it has been suggested that phthalate exposure does not imply a decreased T production in the human fetus (Jensen et al, 2015;Johnson et al, 2012;Spade et al, 2014), DEHP has been reported to decrease T production in the human adult testis (Desdoits-Lethimonier et al, 2012;Hallmark et al, 2007).…”
Section: Discussionmentioning
confidence: 99%